The Prevalence of Multidrug-Resistant (MDR) Pseudomonas aeruginosa Isolated from Patients Suffering from Cystic Fibrosis in the World: A Systematic Review and Meta-Analysis - Jalileh Ebn Abbas; Samaneh Rouhi; Hamed Jafarpour; Khadijeh Taherkhani; Sanaz Ahmadi; Bijan Nouri; Rasool Nasiri Kalmarzi; Farshid Gholami; Arya Jafari; Nasrin Yaghoobi (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Infection caused by Pseudomonas aeruginosa (P. aeruginosa) with multiple drug resistance is one of the most important problems in patients suffering from cystic fibrosis. The purpose of this research is to investigate the prevalence of P. aeruginosa isolated with multiple drug resistance in patients suffering from cystic fibrosis. Materials and Methods: Articles between 2008 and 2022 were searched. To perform the meta-analysis, STATA 14 software was used both in the fixed model and in the random effects model. To check the heterogeneity of the data, the Q-test (p<0.10) was used with the chi-square χ2 distribution at the 95% confidence level. Two-sided statistical tests were performed with α=0.05. Results: The highest (100%, 95% confidence interval (CI): 0.99-1.00) and the lowest (4%, 95% CI: 0.02-0.09) prevalence was in 2021. In cross-sectional studies, the prevalence of 44% (95% CI: 0.21-0.68, odds ratio (OR) = 1.55), and in the cohort, 52% (95% CI: 0.26-0.77, OR = 1.68) was observed. Prevalence of both age groups; <20 (95% CI: 0.09-0.97, OR = 1.7, p = 0.000) and ≥ 20 (95% CI: 76. 0.30-0.76, OR = 1.7, p = 0.000) was 53%. Conclusion: Multiple drug resistance was observed in P. aeruginosa during different years and ages. The findings of this research and the increasing antibiotic resistance of this bacterium indicate the leading challenges in the treatment of patients with cystic fibrosis, which must be properly managed and treated.